2014
DOI: 10.5489/cuaj.1555
|View full text |Cite
|
Sign up to set email alerts
|

Case of emphysematous pyelonephritis in kidney allograft: Conservative treatment

Abstract: Emphysematous pyelonephritis is an acute necrotizing infection with gas in the kidney and perinephric space that carries a bad prognosis. Apart from its predisposing clinical entities, diabetes mellitus and immune-incompetence are quite common in patients with this infection. We report a case of a 53-year-old kidney transplant recipient diabetic male, suffering from recurrent fever, abdominal pain and nausea episodes. Immediate broad-spectrum antibiotics were administered and percutaneous drainage was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…[ 2 ] The only exception to this female predominance is that males undergoing renal transplantation are more likely to suffer. [ 12 ] The most common clinical features in our series and reported by others include fever/chills, flank pain, renal angle tenderness, vomiting, and dysuria. These symptoms and signs are nonspecific and cannot differentiate EPN from the usual pyelonephritis.…”
Section: Discussionsupporting
confidence: 52%
“…[ 2 ] The only exception to this female predominance is that males undergoing renal transplantation are more likely to suffer. [ 12 ] The most common clinical features in our series and reported by others include fever/chills, flank pain, renal angle tenderness, vomiting, and dysuria. These symptoms and signs are nonspecific and cannot differentiate EPN from the usual pyelonephritis.…”
Section: Discussionsupporting
confidence: 52%
“…From the available past literature, there is an ascendancy of EPN in females, owing to their increased perceptivity to UTI [20,21]. The female to male ratio of our cohort is in conjunction to that reported by one of the study, but much higher ratios have been reported previously [22,23]. As per other series, our maximum patients presented with fever with or without flank pain.…”
Section: Discussionsupporting
confidence: 86%
“…Al‐Geizawi classification stage 1 tends to be treated by antibiotics and stage 2 by antibiotics plus percutaneous drainage (PCD) (Table ) . Stage 3 patients are treated either by PCD or nephrectomy, however, some stage 3 cases deteriorated too quickly to perform transplant nephrectomy .…”
Section: Discussionmentioning
confidence: 99%